“Over time it just becomes easier…”: parents of people with Angelman syndrome and Prader–Willi syndrome speak about their carer role - Thomson, Allyson; Glasson, E.; Roberts, P.; Bittles, A. (Informa Healthcare, 2016)
Purpose: This study investigated two of the stresses experienced by parents caring for offspring with Angelman syndrome (AS) and Prader–Willi syndrome (PWS) in Western Australia, and identified their coping strategies. Methods: Parents of 19 offspring with AS and PWS participated in the Family Stress and Coping Interview which provides a stress level score, and a discussion of stressors and coping methods associated with 24 life situations, two of which are reported. All text was examined using directed content analysis. Results: Family carers (14/19) reported high stress associated with the initial diagnosis of AS or PWS in their offspring; and finding time for themselves. Stressors identified included lack of quality information about the disorder, time constraints and physical and emotional tiredness. Parents adopted a variety of coping strategies, including learning about the disorder, accepting the situation, seeking instrumental and social supports and dealing with problems. Conclusions: No specific coping strategy was associated with reduced stress. However, parents felt that accurate and timely information during the diagnostic period helped. Parents used family and community support although there were difficulties accessing respite care. It is advised that government agencies, service providers, family members and peer support associations should provide practical and emotional support to assist the parents of offspring with AS and PWS, and indeed any form of intellectual disability, across the lifespan. Implications for Rehabilitation: Long-term caring for offspring with AS or PWS can involve considerable stress for parents. Stress has been associated with poorer health outcomes for parental carers. Parents need a variety of practical and emotional supports to cope with stress, including timely access to information.